Lingkungan Pendidikan Islam - Imam, Nurul; Ondeng, Syarifuddin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine what the Islamic educational environment is like, its types and influences in the world of Islamic education. The research approach used is a qualitative approach through literature studies. The stages of the study were carried out by collecting literature sources, both primary and secondary. This study classifies data based on the research formula. In the advanced stage, data processing and/or reference citations are carried out to be displayed as research findings, abstracted to obtain complete information, and interpreted to produce knowledge for drawing conclusions. The research instrument is the researcher himself. The results show that the Islamic educational environment is a system that includes all aspects that influence the learning process and character formation of students in Islamic contests. The types of educational environments are divided into three, namely the family environment, the school environment and the community environment. There are three influences in Islamic education, namely negative, positive and neutral influences.